2002
DOI: 10.1590/s0104-66322002000300007
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and simulation of a pseudo-two-phase gas-liquid column reactor for thermal hydrocracking of petroleum heavy fractions

Abstract: -This work presents a model to predict the behavior of velocity, gas holdup and local concentration fields in a pseudo-two-phase gas-liquid column reactor applied for thermal hydrocracking of petroleum heavy fractions. The model is based on the momentum and mass balances for the system, using an Eulerian-Eulerian approach. Using the k-ε model, fluid dynamics accounts for both laminar and turbulent flows, with discrete small bubbles (hydrogen) flowing in a continuous pseudohomogeneous liquid phase (oil and cata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 10 publications
(18 reference statements)
0
5
0
Order By: Relevance
“…Therefore, the dispersion coefficient could be expressed by where μ f is the sum of turbulent and laminar viscosity. This consideration was applied successfully by Matos and Guirardello, Matos et al, in a CFD model for petroleum hydrotreating.…”
Section: Estimation Of Model Parametersmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the dispersion coefficient could be expressed by where μ f is the sum of turbulent and laminar viscosity. This consideration was applied successfully by Matos and Guirardello, Matos et al, in a CFD model for petroleum hydrotreating.…”
Section: Estimation Of Model Parametersmentioning
confidence: 99%
“…Matos and Guirardello 47 presented an isothermal CFD model which includes momentum equations, based on the kinetic network of six lumps presented by Krishna and Saxena 48 for thermal hydrocracking reactions. The lumps are heavy and light aromatics, naphtenes, and paraffins.…”
Section: Energy and Fuelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Various reviews have been reported on hydrocracking technology in the literature. Different aspects of hydrocracking have been discussed, such as types of hydrocracking, process optimization, catalysis, catalyst acidity, pore diffusion, catalyst poisons and reactor type (Ramakanta et al, 2015;Angeles et al, 2014;Ahmed et al, 2013;Valavarasu et al, 2003;Qader and Hill, 1969;Sadighi and Ahmad, 2013;Matos and Guirardello 2002). These authors also emphasized that the available literature on the kinetics of hydrocracking is scarce, and that kinetic aspects and structural modeling needs to be studied in detail.…”
Section: Introductionmentioning
confidence: 99%
“…A few authors have modeled slurry reactors for hydrocracking (HDC) and hydrotreating (HDT) of oil fractions with CFD techniques. Even though these models have shown good results, they are focused on fluid dynamics and on the behavior of hydrodynamic variables; therefore despite being formulated in steady state, they are not capable of simulating and predicting detailed changes in product yields, product properties, mass and energy balances, etc. On the other hand, axial dispersion models (ADM) are the most common ones used in the literature dealing with SPR .…”
Section: Introductionmentioning
confidence: 99%